THE ROLE OF AQUIDOBIONTS IN THE SELF-PURIFICATION OF RESERVOIRS - Nurmatova Rukhsora Utkir kizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Hydrobionts play a key role in the process of self-purification of water bodies. They are an important part of the food chain and are involved in various biochemical processes. Below are the main roles of aquatic organisms in the self-purification of water bodies. In general, aquatic organisms are key participants in the processes of self-purification of water bodies, performing a number of important functions, such as biological decomposition, filtration, biotransformation and oxygen production.